The Audio-lingual Method For The Furtherance Of Reformed Productive Speaking Skill: A Discourse Analysis Approach. - Said, Tarek (جامعة الوادي - University of Eloued, 2022)
The Audio-Lingual method strives for cultivating communicative competence of learners over dialogues. The process of dialogues and pattern drills that learners stipulate to repeat are inclined to construct habits and behaviors in students which will enable them to further active, fast, and automatic reformed responses. Drills are suitable in foreign language teaching contexts on the grounds that they provide learners the occasion to perpetrate what they have detected. In an initial descriptive methodology through which the Audio-Lingual Method can serve to detect the speaking proficiency of learners. Any foreign language needs an oral proficiency that would use it to deliver what you have learnt. The scheme and intention of this article is to establish a correlation between the Audio-Lingual method and reformed productive speaking skill. We may conclude that teachers should boost learners to use the Audio-Lingual method that would be first to assist them enhance their general English speaking proficiency, which embraces different vocabularies and sentence structures. The second aspect would be to thrust them become aware and manipulators of the Audio-Lingual method principles such as repetition drills, transformation drills and dialogue memorization.
مقال
Keywords: Approach ; Audio-Lingual Method ; Communication ; Pattern drills ; Speaking skill